Turkish-Islamıc Type Management Scale Through The Nizamülmülk Ideas - ŞEN, Alper Tunga; TAN, Zehra (Afyon Kocatepe Universitesi Iktisadi ve Idari Bilimler Fakultesi Dergisi, 2023)
Management science emerged as a field that attracts much attention and where different management models are constantly being researched. As a result, scientists are frequently on the agenda and conduct several in-depth studies to develop a better or more ideal management model. The primary purpose of this article is to create a valid and trustworthy seven-dimensional scale to introduce a new management model to the literature. The scale has a unique value in that it fully covers the seven various sub-dimensions it takes and that it is performed for the first time. After the analysis, it was confirmed that it was an appropriate and explanatory scale consisting of 32 items and seven sub-dimensions. The article ends by discussing the theoretical and practical results and making suggestions for future research.
Keywords: Public Administration; HF5001-6182; Siyasetname; Yönetim; Yönetim Modeli; Nizamülmülk; Siyasetname.; Nizamülmülk; Social Sciences; Management; Yönetim Modeli; Kamu Yönetimi; Management Model; H; Management; Management Model; Nizamülmülk; Siyasetname; Yönetim; Business; 9. Industry and infrastructure; 4. Education; 1. No poverty; 12. Responsible consumption; 11. Sustainability; 8. Economic growth